Quaker Epistemology - Rediehs, Laura (Brill research perspectives in quaker studies, 2019)
Quakerism emerged in the seventeenth century, during a time when philosophical debates about the nature of knowledge led to the emergence of modern science. The Quakers, in some conversation with early modern philosophers, developed a distinctive epistemology rooted in their concept of the Light Within, which functioned as a special internal sense giving access to divine insight. The Light Within provided illumination both to properly understand the Bible and to ‘read’ the Book of Nature. This epistemology can be thought of as an expanded experiential empiricism that integrates our ethical and religious knowledge with our scientific knowledge. This epistemology has carried through in Quaker thought to the present day and can be helpful in the context of today’s epistemological crisis.